Re-Inventing Public Services Using Gamification Approaches - Buheji, Mohamed (International Journal of Economics and Financial Issues, 2019)
Gamification is still an emerging field in social sciences with a growing interest in its application in public services. Yet, most of the published literature on gamification focus on the utilisation of electronic games and serious games as a methodology for the development of public services; rather than seeing how to apply gamification approaches in developing these services. Thus the rationale for this paper is to develop the capacity of the public sector to re-invent itself through the utilisation of gamification. This qualitative research aims to provide a theoretical framework for gamification approaches in the different sectors of the public services through enhancing the engagement of the stakeholders of these services. The findings show the opportunities for the government transformation that could come from gamifying essential sectors like education, water utility services, labour management, women affairs, traffic management, sewage and sanitary service, social insurance, police services and justice and legal affairs. The study concludes with recommendations for further empirical studies that would enhance the integration of gamification approaches in re-inventing the public services. Keywords: Gamification, Social Change, Continual Improvement, Inspiration Labs, Re-Inventing Public Services, Socio-Economic Transformation JEL Classification: O35 DOI: https://doi.org/10.32479/ijefi.8803